A silicododecamolybdate/pyridinium-tetrazole hybrid molecular salt as a catalyst for the epoxidation of bio-derived olefins - Nunes, Martinique S. (2021)
The hybrid polyoxometalate (POM) salt (Hptz)(4)[SiMo12O40].nH(2)O (1) (ptz = 5-(2-pyridyl)tetrazole) has been prepared, characterized by X-ray crystallography, and examined as a catalyst for the epoxidation of cis-cyclooctene (Cy) and bio-derived olefins, namely dl-limonene (Lim; a naturally occurring monoterpene found in the rinds of citrus fruits), methyl oleate and methyl linoleate (fatty acid methyl esters (FAMEs) obtained by transesterification of vegetable oils). The crystal structure of 1 consists of alpha-Keggin-type heteropolyanions, [SiMo12O40](4-), surrounded by space-filling and charge-balancing 2-(tetrazol-5-yl)pyridinium (Hptz(+)) cations, as well as by a large number of water molecules of crystallization (n = 9). The water molecules mediate an extensive three-dimensional (3D) hydrogen-bonding network involving the inorganic anions and organic cations. For the epoxidation of the model substrate Cy in a nonaqueous system (tert-butylhydroperoxide as oxidant), the catalytic performance of 1 (100% epoxide yield at 24 h, 70 degrees C) was superior to that of the tetrabutylammonium salt (Bu4N)(4) [SiMo12O40] (2) (63% epoxide yield at 24 h), illustrating the role of the counterion Hptz(+) in enhancing catalytic activity. The hybrid salt 1 was effective for the epoxidation of Lim (69%/85% conversion at 6 h/24 h) and the FAMEs (87-88%/100% conversion at 6 h/24 h), leading to useful bio-based products (epoxides, diepoxides and diol products).